La peur du prolétaire et les paradoxes du socialisme shavien dans Widowers’ Houses - Stéphane Guy (Cahiers Victoriens et Edouardiens)
As a socialist reformer and critic of revolutionary Marxism, the Fabian Bernard Shaw was intent on entrusting the middle-class bourgeoisie with the march to collectivism. His first dramatic work, Widowers’ Houses, is pervaded with the ambivalence underlying such a stance. Beyond the fear that is represented throughout and the dread of capitalism that it seeks to bring about among the Victorian public, the play builds up a dramaturgy of threat, breaking with the fashionable theatres of late nineteenth century London and paradoxically making the proletarian into both a victim and symptom of capitalist immorality.